Centrifugal Fans and Their Use in Bleeder Applications - David W. Kennedy; Stephen P. Harrison (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
In the past few years, a new system has been developed for ventilating longwall panels in some gassy coal mines in the Northern West Virginia area. This system utilizes a five or six foot diameter air shaft to ventilate a group of three or more longwall panels dependent on conditions. This shaft exhausts all the air needed to, ventilate the active longwall and adjacent gob areas. By law, this bleeder fan can handle double the maximum methane concentration allowed in a normal return air course. As a result, the methane that must be diluted by the primary ventilation circuits is reduced. This new ventilation system was first conceived by mine management as a means of coping with a sudden shift in production mode that occurred a few years ago. Formerly, production often consisted of room and pillar mining with continuous miners. The high methane liberation rate was handled by driving entries around a large block of coal prior to mining. This isolated the future mining area from the adjacent coal seam and allowed a major portion of the trapped in situ methane to bleed off. Also, these bleeders served to exhaust return air from the mining area. Once the bleeders were established, productive mining could start. When the decision was made to shift production mode from continuous miners to longwall mining, some of the bleeders did not encompass large enough unmined areas under the old ventilation system to initiate longwall production. Also, many other established continuous miner section bleeders were either improperly positioned or too restricted for longwall ventilation. Unfortunately, standard bleeder development can take up to two years' time. In order to eliminate the old style bleeder system and maintain or increase the margin of safety for ventilation, the bleeder shaft system was conceived. With this system, the only entries developed are those necessary for the longwall, significantly reducing the production delay. In this area, the Pittsburgh #8 coal seam dips to the northwest. As a result of this dip, the bleeder shaft is constructed in the northernmost set of tailgate entries. In this manner, groundwater accumulations can be pumped to the surface and bleeder entries kept dry. During the initial longwall entry development, the bleeder fan can be used to ventilate entries adjacent to virgin coal where significant methane liberation often occurs. Once longwall production starts, the bleeder shaft exhausts the entire air quantity necessary to safely ventilate the longwall. As the bleeder entries deteriorate, the air quantity and pressure characteristics must be increased. The extreme flexibility of the centrifugal fan used at the surface allows the air quantity and pressure to be adjusted without stopping the fan. This improves safety by decreasing the possibility of a methane buildup resulting from the fan being out of service. The bleeder shaft system of ventilation, developed by mine management in Northern West Virginia, can provide a safe means for effectively ventilating longwall panels in excessively gassy mines. This system should be considered where mining conditions are comparable.